Phylosophical-legal analysis of the concept «information» in the modern context - Kushakova-Kostytska, Nataliia V. (Journal of the Belarusian State University. Law, 2019)
The article is devoted to the study of the philosophical and legal content of the concept of «information» in the aspect of worldview factors that are characteristic of the information society as a modern era of development of human civilization. The author pays special attention to issues related to the definition of general principles for the emergence and development of the concept of «information», as well as its transformation into a general scientific category, which methodologically influences the development of all spheres of scientific activity, including in the field of philosophy and law.
Keywords: informatics; information; information society; cybernetics; knowledge society; programming